Single-Cell RNA Sequencing Reveals the Difference in Human Normal and Degenerative Nucleus Pulposus Tissue Profiles and Cellular Interactions - Li, Zhencong; Ye, Dongping; Dai, Libing; Xu, Yude; Wu, Hao; Luo, Wei; Liu, Yiming; Yao, Xiguan; Wang, Peigeng; Miao, Haixiong; Xu, Jiake; Liang, Weiguo (Frontiers in Cell and Developmental Biology, 2022)
Background: The nucleus pulposus is a constituent structure of the human intervertebral disc, and its degeneration can cause intervertebral disc degeneration (IDD). However, the cellular and molecular mechanisms involved remain elusive. Methods: Through bioinformatics analysis, the single-cell transcriptome sequencing expression profiles of human normal nucleus pulposus (NNP) cells and human degenerative nucleus pulposus (DNP) cells were compared to clarify the transcriptome differential expression profiles of human NNP and DNP. The single-cell sequencing results of the two samples were analyzed using bioinformatics methods to compare the differences in histiocytosis between human NNP and DNP, map the histiocytes of NNP and DNP, perform cell differentiation trajectories for the cell populations of interest and predict cell function, and explore their heterogeneity by pathway analysis and Gene Ontology analysis. Results: Nine cell types were identified, which were chondrocyte 1, chondrocyte 2, chondrocyte 3, chondrocyte 4, chondrocyte 5, endothelial, macrophage, neutrophil, and T cells. Analysis of the proportion of chondrocytes in different tissues revealed that chondrocyte 1 accounted for a higher proportion of NNP cells and highly expressed COL2A1 compared with DNP cells; chondrocyte 2, chondrocyte 3, chondrocyte 4, and chondrocyte 5 accounted for a higher proportion of DNP cells compared with NNP cells. Among them, chondrocyte 2 was an inhibitory calcified chondrocyte with high expression of MGP, chondrocytes 3 were fibrochondrocytes with high expression of COL1A1, chondrocytes 4 were chondrocytes that highly express pain inflammatory genes such as PTGES, and chondrocytes 5 were calcified chondrocytes with high expression of FN1 (chondrocytes 4 and chondrocytes 5 were found for the first time in a study of single-cell transcriptome sequencing of disc tissue). Cell trajectory analysis revealed that chondrocyte 1 was at the beginning of the trajectory and chondrocyte 3 was at the end of the trajectory, while chondrocyte 5 appeared first in the trajectory relative to chondrocyte 2 and chondrocyte 4. Conclusion: After functional identification of the specifically expressed genes in five chondrocytes, it was found that chondrocyte 1 was a chondrocyte with high expression of COL2A1, COL9A2, COL11A2, and CHRDL2 in a high proportion of NNP cells, and chondrocyte 3 was a fibrochondrocyte with high expression of COL1A1, COL6A3, COL1A2, COL3A1, AQP1, and COL15A1 in an increased proportion during nucleus pulposus cell degeneration. Through cell trajectory analysis, it was found that chondrocytes 5 specifically expressing FN1, SESN2, and GDF15 may be the key cells leading to degeneration of nucleus pulposus cells. Chondrocytes 2 expressing MGP, MT1G, and GPX3 may play a role in reversing calcification and degeneration, and chondrocytes 4 expressing PTGES, TREM1, and TIMP1 may play a role in disc degeneration pain and inflammation.